Analisa Kompetensi Alumni Pendidikan Matematika menggunakan Discrapancy Evaluation Model - Rita Sari; Srimuliati (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2019)
The curriculum is an important element in education and the basic framework is also an indicator of the progress of education. So important was the curriculum that the Government continuously continued to make curriculum changes from 1975 to the present. Therefore every educational institution must have a curriculum including LAIN IAIN as one of the Universities that produce prospective educators especially mathematics teachers at the level of junior and senior high school education units in Langsa city. But in reality, there are a lot of PMA Study Program alumni who work not following their scientific fields. The purpose of this study was to determine the design of PMA Study Program curriculum in meeting the needs of the labour market for alumni. This study uses discrepancy evaluation models (DEM). The results showed that stakeholders considered that a portion of PMA Study Program alumni was less competent at work. so it is necessary to do a curriculum change, especially in the distribution of subjects by taking into account the curriculum needs of the school level and the job market.